Production of quasi-2D platelets of nonlayered iron pyrite (FeS2) by liquid-phase exfoliation for high performance battery electrodes - Kaur, Harneet; Tian, Ruiyuan; Roy, Ahin; McCrystall, Mark; Horvath, Dominik Valter; Lozano Onrubia, Guillermo; Smith, Ross; Ruether, Manuel; Griffin, Aideen; Backes, Claudia; Nicolosi, Valeria; Coleman, Jonathan N. (ACS nano, 2020)
Over the past 15 years, two-dimensional (2D) materials have been studied and exploited for many applications. In many cases, 2D materials are formed by the exfoliation of layered crystals such as transition-metal disulfides. However, it has recently become clear that it is possible to exfoliate nonlayered materials so long as they have a nonisotropic bonding arrangement. Here, we report the synthesis of 2D-platelets from the earth-abundant, nonlayered metal sulfide, iron pyrite (FeS2), using liquid-phase exfoliation. The resultant 2D platelets exhibit the same crystal structure as bulk pyrite but are surface passivated with a density of 14 × 1018 groups/m2. They form stable suspensions in common solvents and can be size-selected and liquid processed. Although the platelets have relatively low aspect ratios (∼5), this is in line with the anisotropic cleavage energy of bulk FeS2. We observe size-dependent changes to optical properties leading to spectroscopic metrics that can be used to estimate the dimensions of platelets. These platelets can be used to produce lithium ion battery anodes with capacities approaching 1000 mAh/g.
In FeS2 ist die Ziffer "2" tiefgestellt
Gesehen am 25.01.2021